ANALYSIS OF CATTLE FEEDING CONDITIONS. (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
he article discusses the impact of animal feeding on their metabolism, milk production levels, and overall health. It analyzes the compliance of feed rations with the norms of feed units, dry matter, fiber, and essential nutrients (protein, calcium, phosphorus, carotene, etc.).